Sedimentation Engineering - Amini, Ata (IntechOpen, 2018)
The lack of knowledge about sedimentation processes taking place in a watershed or a waterbody hinders practical progress in addressing problem-solving. To assist the reader in putting sediment quantity and quality issues into perspective, sedimentation engineering features the most state-of-the-art contributions from a number of researchers working in the fields of water resources and soil erosion. The book contains 10 chapters selected among a great number of submitted manuscripts. The main topics are sedimentation processes in marshes, harbor estuaries, gulf, hydraulic turbine, and volcanic area. Sediment contamination and few other topics are included as well. The case studies cover a sequence for integrated solutions where watershed management and sedimentation engineering are not decoupled. This book on sedimentation engineering is designed for researchers and professionals and for course use in environmental science.